Affective Assessment Instrument Based on Krathwohl-Anderson Taxonomy in Senior High School - Sri Mundarti; Febri Tia Aldila (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aims to develop an affective assessment instrument based on Krathwohl-Anderson taxonomy in class XI on hydrocarbons and petroleum and to find out the teacher's response to an affective assessment instrument based on Krathwohl-Anderson taxonomy in class XI on hydrocarbons and petroleum. Methodology: This research is a development research with the ADDIE development model. This research was conducted at SMAN Titian Teras Jambi with 10 class XI teachers as subjects who were obtained by purposive sampling technique. The instrument in this study was a teacher response instrument in which quantitative and qualitative data were processed using descriptive statistics and the Miles and Huberman technique. Main Findings: The affective assessment instrument based on Krathwohl-Anderson taxonomy in class XI on the developed hydrocarbon and petroleum material was declared valid and feasible to use. Furthermore, the teacher gave a very good response with a percentage of 60% towards the affective assessment instrument based on the Krathwohl-Anderson taxonomy. Novelty/Originality of this study: The latest update in this research is to develop an affective assessment instrument based on the Krathwohl-Anderson taxonomy on hydrocarbon and petroleum materials. There are no studies on the development of affective assessment instruments based on the Krathwohl-Anderson taxonomy. Therefore, this study complements previous studies.